Abject Objects: A Case for Using Humour and Horror in Design - Taylor, Megan (Design Journal, 2026)
This paper explores the possibility of combining theories from different subject areas into product design as influences that are not typically seen in this space. The main aim of this research was to discover whether concepts from horror and comedy could be incorporated into a design process in order to create products that influence user reactions in new ways. While this paper only explores one example of incorporating new influences into a design process, it covers some of the key ideas in relation to wider exploration of concepts and how the ideas presented may work with other disciplinary themes. An exploration of user interactions with products in general was also key in understanding how this could affect the way users viewed and interacted with the final products. Finally, this paper proposes these ideas as a way to open new critiques on the design world and the influences used when designing new products. Building on research into horror and humour concepts, this paper explores the integration of these into a product design process. Walking through each stage of a design process drawing from academic perspectives on what makes a product design process successful. This paper demonstrates how a design process can be altered by introducing new influences while still meeting guidelines for what good design is. By then undertaking the design process and thus creating a suite of products demonstrating the concepts that were introduced, the paper determines that products designed with alternative influences can have a space in the design world and can function and interact with users in new ways. The implications of this research open possibilities of successfully using uncommon influences in product design as a way to open new understandings of what good design can be.